2015
DOI: 10.1097/pcc.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Veno-Venous Hemodiafiltration and Plasma Exchange in Infantile Acute Liver Failure

Abstract: Our multidisciplinary approach for infants with acute liver failure achieved favorable outcomes. Further investigations are needed to examine the efficacy of the artificial liver support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 24 publications
1
48
0
1
Order By: Relevance
“…Several studies to date have suggested improved survival in liver failure patients treated with CRRT, with the possibility that the greatest benefit is achieved with high-intensity therapy [2,7,9,10,13,14.] These studies, however, have been of limited quality and have been almost entirely single-center, retrospective cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies to date have suggested improved survival in liver failure patients treated with CRRT, with the possibility that the greatest benefit is achieved with high-intensity therapy [2,7,9,10,13,14.] These studies, however, have been of limited quality and have been almost entirely single-center, retrospective cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, intensive correction of ammonia levels is possible using CRRT, and has been associated with improved survival [7,8]. Furthermore, high volume hemofiltration has been associated with improved survival in children with liver failure [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported our single-center experience with patients with acute liver failure [13, 14]. Of the 65 patients treated at our center for acute liver failure between November 2005 and December 2015, 54 patients (83.1%) received liver transplants.…”
Section: Liver Transplantsmentioning
confidence: 99%
“…Both CVVHDF and PE were initially carried out for all patients under mechanical ventilation to identify the precipitating cause of liver failure; once the cause of ALF was determined, specific therapy was initiated. The details of CVVHD and PE have been described elsewhere . During intubation, the severity of HE was continuously monitored by electroencephalogram.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, therapeutic apheresis and dialysis have been uniquely developed and established as artificial liver support therapy in a combination of continuous veno‐venous hemodiafiltration (CVVHDF) and plasma exchange (PE) . As the deceased organ donation rate in Japan has remained low, living donor LT has been mainly undertaken for patients refractory to the above treatment .…”
Section: Introductionmentioning
confidence: 99%